Chronic adherence to a ketogenic diet modifies iron metabolism in elite athletes - McKay, A. K. A.; Peeling, P.; Pyne, D. B.; Welvaert, M.; Tee, N.; Leckey, J. J.; Sharma, A. P.; Ross, M. L. R.; Garvican-Lewis, L. A.; Swinkels, D. W.; Laarakkers, C. M.; Burke, L. M. (Medicine & Science in Sports & Exercise, 2019)
Purpose The short-term restriction of carbohydrate (CHO) can potentially influence iron regulation via modification of postexercise interleukin-6 (IL-6) and hepcidin levels. This study examined the effect of a chronic ketogenic low-CHO high-fat (LCHF) diet on iron status and iron-regulatory markers in elite athletes.